City of Greenville’s Social Media in times of emergencies - Hawley, Steve (My University, 2013)
Steve Hawley is communications manager and public information officer for the City of Greenville where his work has won Excellence in Communications Awards from North Carolina City and County Communicators. He is the host of the city of Greenville's public-access television show "City Scene.
Keywords: Hurricanes; Emergency management; NCEM; Emergency disaster